The clinical case of cardiac amyloidosis associated with multiple myeloma - E. I. Tsoi; Yu. V. Rogovskaya; S. V. Demyanov; V. V. Ryabov (Бюллетень сибирской медицины, 2020)
This clinical case demonstrates the difficulty of timely intravital diagnosis of cardiac amyloidosis and the prescription of adequate drug therapy which is associated not only with the limited possibilities of  establishing a correct diagnosis and the absence of specific treatment in most cases, but also with a delay in seeking medical care. Thus, development and improvement of non-invasive screening methods of examination will allow to identify this pathology at earlier stages with a possibility of prescribing effective drugs and performing heart transplantation in some cases.